Global Dexterity - Molinsky, Andy (Harvard Business Review Press, 2013)
What does it mean to be a global worker and a true "citizen of the world" today? It goes beyond merely acknowledging cultural differences. In reality, it means you are able to adapt your behavior to conform to new cultural contexts without losing your authentic self in the process. Not only is this difficult, it's a frightening prospect for most people and something completely outside their comfort zone. But managing and communicating with people from other cultures is an essential skill today. Most of us collaborate with teams across borders and cultures on a regular basis, whether we spend our time in the office or out on the road. What's needed now is a critical new skill, something author Andy Molinsky calls "global dexterity." In this book Molinsky offers the tools needed to simultaneously adapt behavior to new cultural contexts while staying authentic and grounded in your own natural style. Based on more than a decade of research, teaching, and consulting with managers and executives around the world, this book reveals an approach to adapting while feeling comfortable--an essential skill that enables you to switch behaviors and overcome the emotional and psychological challenges of doing so. From identifying and overcoming challenges to integrating what you learn into your everyday environment, Molinsky provides a guidebook--and mentoring--to raise your confidence and your profile. Practical, engaging, and refreshing, "Global Dexterity" will help you reach across cultures--and succeed in today's global business environment.